FROM AN OLD TECHNO-SCIENTIFIC DREAM TO TODAY’S REALITY: ARTIFICIAL INTELLIGENCE IN HEALTHCARE BETWEEN HORROR AND ENCHANTMENT - RIALLE, Vincent (MEDECINE LEGALE DROIT MEDICAL, 2025)
Artificial Intelligence in Healthcare (AIH) is currently undergoing exceptional developments and questioning. This article presents them in two parts. First, it describes the years of awakening of AIH, outlining its historical, scientific and ideological basis, which is based on the figure of the “expert” and the omnipotence of purely logic-deductive reasoning. Second, the shift towards today’s mass artificial intelligence, which is based on a phenomenal and omnipresent computational power. This evolution juxtaposes impressive medical and social progress with dramatic excesses. In a path littered with challenges, AIH is making a major contribution to the understanding of diseases and the discovery of treatments, as well as to the establishment of a vast, coherent and secure infrastructure for access to health for all, with a highly universal focus. Based in particular on the French case, representative of an alliance between science and social and environmental progress, the article presents and illustrates this path. It then opens the drifts page, and shows how unregulated “Big Data” constantly uses formidable algorithms of control over individuals, increases inequalities, causes crystallization on delusional opinions, degrades capacities for dialogue and mutual understanding, and undermines democratic processes. The conclusion opens up a promising future in terms of medical health, social progress and democracy, but on condition of urgently cleaning up the Internet and Big Data of mass manipulation and alienation algorithms.